Advancing improvement in riverine water quality caused a non-native fish species invasion and native fish fauna recovery - Łukasz Głowacki (Nature Portfolio, 2021)
Abstract The knowledge of biotic and abiotic drivers that put non-native invasive fishes at a disadvantage to native ones is necessary for suppressing invasions, but the knowledge is scarce, particularly when abiotic changes are fast. In this study, we increased this knowledge by an analysis of the biomass of most harmful Prussian carp Carassius gibelio in a river reviving from biological degradation. The species' invasion followed by the invasion's reversal occurred over only two decades and were documented by frequent monitoring of fish biomass and water quality. An initial moderate improvement in water quality was an environmental filter that enabled Prussian carp’s invasion but prevented the expansion of other species. A later substantial improvement stimulated native species’ colonization of the river, and made one rheophil, ide Leuciscus idus, a significant Prussian carp’s replacer. The redundancy analysis (RDA) of the dependence of changes in the biomass of fish species on water quality factors indicated that Prussian carp and ide responded in a significantly opposite way to changes in water quality in the river over the study period. However, the dependence of Prussian carp biomass on ide biomass, as indicated by regression analysis and analysis of species traits, suggests that the ecomorphological similarity of both species might have produced interference competition that contributed to Prussian carp’s decline.